2011
DOI: 10.1073/pnas.1101398108
|View full text |Cite
|
Sign up to set email alerts
|

Functional CD47/signal regulatory protein alpha (SIRPα) interaction is required for optimal human T- and natural killer- (NK) cell homeostasis in vivo

Abstract: The homeostatic control mechanisms regulating human leukocyte numbers are poorly understood. Here, we assessed the role of phagocytes in this process using human immune system (HIS) BALB/c Rag2 −/− IL-2Rγc −/− mice in which human leukocytes are generated from transplanted hematopoietic progenitor cells. Interactions between signal regulatory protein alpha (SIRPα; expressed on phagocytes) and CD47 (expressed on hematopoietic cells) negatively regulate phagocyte activity of macrophages and other phagocytic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
155
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(167 citation statements)
references
References 39 publications
(71 reference statements)
8
155
0
1
Order By: Relevance
“…[31][32][33] A recent study also showed that transgenic expression of mouse CD47 into CD34 ϩ CD38 Ϫ human fetal liver cells significantly enhanced the human cell engraftment into BALB-RG mice. 34 Based on these data, the binding of NOD-SIRPA with human CD47 might produce signals for mouse macrophages not to engulf human HSCs, which presumably makes the strain permissive for human HSC engraftment. 24 The most important question was whether the NOD-specific highly efficient human cell engraftment in vivo could be explained solely by the NOD-Sirpa polymorphism.…”
mentioning
confidence: 99%
“…[31][32][33] A recent study also showed that transgenic expression of mouse CD47 into CD34 ϩ CD38 Ϫ human fetal liver cells significantly enhanced the human cell engraftment into BALB-RG mice. 34 Based on these data, the binding of NOD-SIRPA with human CD47 might produce signals for mouse macrophages not to engulf human HSCs, which presumably makes the strain permissive for human HSC engraftment. 24 The most important question was whether the NOD-specific highly efficient human cell engraftment in vivo could be explained solely by the NOD-Sirpa polymorphism.…”
mentioning
confidence: 99%
“…Indeed transgenic or congenic expression of either the human or the NOD SIRP [10,11], or mouse CD47 gene transfer into reconstituting human hematopoietic cells GM-CSF and TPO [13]. These MISTRG mice developed myeloid and NK cells more efficiently than NSG mice, but still a significant variation in human immune system component reconstitution could be observed.…”
Section: Mice With Reconstituted Human Immune System Components As Momentioning
confidence: 99%
“…In contrast, BRG mice are usually less well reconstituted with human immune system components, often reaching only 10% of human hematopoietic cells in the peripheral blood after 3 months [10,11]. Xenoreactivity of the mouse myeloid compartment against the engrafting human cells was identified as the limiting factor.…”
Section: Mice With Reconstituted Human Immune System Components As Momentioning
confidence: 99%
“…38 The second study showed that retrogenic expression of murine CD47 in human HSC prior to transplantation significantly improved human immune system development. 37 Overall, these studies highlight the importance of strain selection in the efficient generation of humanized mice.…”
Section: Strain Development For Humanized Micementioning
confidence: 99%
“…Two recent studies using distinct approaches have demonstrated that the SIRPa-CD47 interactions are critically important for the engraftment of human HSC and immune cell development in IL2rc null mice. 37,38 It was first shown that transgenic expression of human SIRPa by mice on a mixed (1293BALB/c) strain background significantly improved the engraftment of human HSC. 38 The second study showed that retrogenic expression of murine CD47 in human HSC prior to transplantation significantly improved human immune system development.…”
Section: Strain Development For Humanized Micementioning
confidence: 99%